PELATIHAN KETERAMPILAN PUBLIC SPEAKING UNTUK SISWA SMAN 28 KABUPATEN TANGERANG - Bakti Abdillah Putra (As-Sidanah, 2025)
Students are not only involved in academic activity at school. They also need to develop themselves in leadership and confidence. Public speaking is one of the skills that help them in self-actualizing which motivated the researcher to conduct a workshop. “Public Speaking for Youth” was held at SMAN 28 Tangerang Regency to elevate student’s ability in public speaking and to build their confidence when they communicate. As part of Generation z, they still cannot handle their insecurities. However, this training prepared the students with techniques to avoid nervousness, effective communication and presentation skills. Students were involved in the lecture, interactive discussion, practical activity, and did the evaluation. The author spread some questionnaire to student which results were processed with descriptive analysis. They appeared with enthusiasm and applied the theory in a structured and convincing performance. The results showed that students felt more confident to speak in front of audience and they consider this training is very satisfactory, even though they expected some more time for the duration. This training would not be successful without the collaboration between facilitator, university, and school who commit to support our young generation. Public Speaking for Youth is expected to be the first step for students to develop their communication skills and to be an individual who are fearless to speak in any situation.